Reforming Infrastructure : Privatization, Regulation, and Competition - Kessides, Ioannis N. (Washington, DC: World Bank and Oxford University Press, 2013)
Infrastructure industries and services are crucial for generating economic growth, alleviating poverty, and increasing international competitiveness. Safe water is essential for life, and health. Reliable electricity saves businesses and consumers from having to invest in expensive backup systems, or more costly alternatives, and keeps rural women and children from having to spend long hours fetching firewood. Widely available and affordable telecommunications and transportation services can foster grassroots entrepreneurship, and thus are critical to generating employment, and advancing economic development. In most developing and transition economies, private participation in infrastructure, and restructuring have been driven by the high costs, and poor performance of state-owned network utilities. Under state ownership, services were usually under-priced, and making it difficult to expand services. The report indicates that although privatization, competitive restructuring, and regulatory reforms improve infrastructure performance, several issues must be considered and conditions met for these measures to achieve their public interest goals. First, reforms have significantly improved performance, leading to higher investment, productivity, and service coverage and quality. Second, effective regulation-including the setting of adequate tariff levels-is the most critical enabling condition for infrastructure reform. Regulation should clarify property rights, and assure private investors that their investments will not be subject to regulatory opportunism. Third, for privatization to generate widely shared social benefits, infrastructure industries must be thoroughly restructured and able to sustain competition. Thus restructuring, to introduce competition should be done before privatization, and regulation should be in place to assure potential buyers of both competitive, and monopoly elements.